Synthesis, modification and graft polymerization of magnetic nano particles for PAH removal in contaminated water - Torabian, Azadeh (BioMed Central, 2014)
Magnetic nanoparticles (MNPs) were modified with 3-Mercaptopropytrimethoxysiline (MPTMS) and grafted with allyl glycidyl ether for coupling with beta naphtol as a method to form a novel nano-adsorbent to remove two poly aromatic hydrocarbons (PAHs) from contaminated water. The modified MNPs were characterized by transmission electron microscopy, infrared spectroscopy and thermogravimetric analysis. Results showed that the modified MNPs enhanced the process of adsorption. Tests were done on the adsorption capacity of the two PAHs on grafted MNPs; factors applied to the tests were temperature, contact time, pH, salinity and initial concentration of PAHs. Results revealed that adsorption equilibrium was achieved in 10 min, and the maximum adsorption capacity was determined as 4.15 mg/g at pH = 7.0 and 20°C. The equilibrium adsorption data of the two PAHs by the modified MNPs were analyzed by Langmuir, Freundlich and Temkin models. Equilibrium adsorption data was determined from the Langmuir, Freundlich and Temkin constants from tests under conditions of pH = 7 and temperature 20°C. Analysis of the adsorption-desorption process indicated that the modified MNPs had a high level of stability and good reusability. Magnetic separation in these tests was fast and this shows that the modified MNPs have great potential to be used as a new adsorbent for the two PAHs removal from contaminated water in water treatment.